The Urgency of Sex Education in Primary School - Muhammad Sofyan Lubis; Muhammad Halimi (International Conference on Elementary Education, 2023)
One of the problems that shake the world of education in Indonesia today is the problem of sexual violence against children. Children have always been a vulnerable object for perpetrators of sexual crimes. In terms of law enforcement, it has not been successful in dealing with this problem. So the only way is through education. Education serves to provide sexual knowledge for children. This means that children are no longer protected, but protect themselves with their knowledge. Sexual knowledge will be able to fortify children by recognizing symptoms that can occur anytime and anywhere against them of sexual deviations from adults. So, in this writing, the author aims to explain how important sexual knowledge is for children, especially for elementary school age children. The age range of children during elementary school education is very suitable to be equipped with various knowledge about the world of sexuality, of course with their age level and thinking ability to understand it. In selecting the method, the author chose to use the Literature Study Research Method. The author will summarize various theories about the importance of sexual knowledge for children. With this writing, it is hoped that policy makers will begin to pay serious attention to how important it is that sexuality knowledge and materials are included in elementary school learning.